Changes in health-related quality of life as a marker in the prognosis in COPD patients. Issue 1 (10th January 2022) - Esteban, Cristóbal; Arostegui, Inmaculada; Aramburu, Amaia; Moraza, Javier; Aburto, Myriam; Aizpiri, Susana; Chasco, Leyre; Quintana, José M.
Chronic obstructive pulmonary disease (COPD) is understood as a complex, heterogeneous and multisystem airway obstructive disease. The association of deterioration in health-related quality of life (HRQoL) with mortality and hospitalisation for COPD exacerbation has been explored in general terms. The specific objectives of this study were to determine whether a change in HRQoL is related, over time, to mortality and hospitalisation. Overall, 543 patients were recruited through Galdakao Hospital's five outpatient respiratory clinics. Patients were assessed at baseline, and the end of the first and second year, and were followed up for 3 years. At each assessment, measurements were made of several variables, including HRQoL using the St George's Respiratory Questionnaire (SGRQ). The cohort had moderate obstruction (forced expiratory volume in 1 s 55% of the predicted value). SGRQ total, symptoms, activity and impact scores at baseline were 39.2, 44.5, 48.7 and 32.0, respectively. Every 4-point increase in the SGRQ was associated with an increase in the likelihood of death: "symptoms" domain odds ratio 1.04 (95% CI 1.00–1.08); "activity" domain OR 1.12 (95% CI 1.08–1.17) and "impacts" domain OR 1.11 (95% CI 1.06–1.15). The rate of hospitalisations per year was 5% (95% CI 3–8%) to 7% (95% CI 5–10%) higher for each 4-point increase in the separate domains of the SGRQ. Deterioration in HRQoL by 4 points in SGRQ domain scores over 1 year was associated with an increased likelihood of death and hospitalisation. In the short term, HRQoL changes in the evaluation of COPD patients can be used as a warning tool for prognosis of hospitalisations and mortality https://bit.ly/3m3kqtc